Active and Healthy Lifestyle – Nationwide Programs in Israeli Schools. (3rd July 2017) - Zach, Sima; Inglis, Varda; Zeev, Aviva; Arnon, Michal; Netz, Yael
Summary: The World Health Organization (WHO) announced the 'Global School Health Initiative' in 1995 following recommendations formulated in the Ottawa Charter for Health Promotion. Hence, the aims of the present study were to describe the various programs for nurturing an active and healthy lifestyle implemented during 2011–12 in schools in Israel, and to identify variables that may explain the success versus lack of success in implementing these programs. Participants were a nationwide representative sample of 126 school principals from six supervisory districts of the Ministry of Education, including six sectors, from the elementary, junior-high and senior-high school levels. Semi-structured telephone interviews were recorded and processed using the ATLAS.ti software for qualitative analysis. Physical education teachers, sciences teachers and social coordinators led the programs' implementation. The programs included four main activities domains: health, physical education, nutrition and sustainability. Three types of program implementation were observed: leading principles, teaching methods, and external programs. Parents were involved mostly in elementary schools. Evidence of program integration into school life was presented by changes in children's behaviors, whereas difficulties stemmed from lack of budget and teaching hours. Science and physical education lessons constituted the anchor for the programs. The schools needed a committed leader to help conduct and maintain the program. Thus, the role of the school principal was to initiate the idea of developing a program, encourage its implementation, select a leader for the program, and then, most importantly, to reinforce the teachers' enthusiasm.